Analysis of the Russian industry development in the context of import substitution - M. A. Korkin (Управление)
The effective development of Russian industry plays a leading role in the country’s economy. The article is devoted to the study of the effective development of the Russian industry at a difficult stage of countering sanctions and the conditions of import substitution. The author explores the development of Russian industrial production in the regions in modern realities and the prospects for its development in the context of import substitution. The introduction presents a scientific literature overview of the research economists studying the problem of industrial production, and formulates the goals and objectives of the work. The purpose of the article is to assess the state of the Russian industry in the difficult conditions of re-equipment and reconfiguration of production processes for import substitution. The dynamics of indices characterizing industrial production in various areas is considered. The factors that have a positive and negative impact on the effective development of Russian industry in recent years have been identified. Based on the conducted research, a general conclusion is formulated that it is expedient for the country to support industrial production for its effective development.